Evaluating the impact of planting dates on seed cotton production across diverse cultivars under variable temperature conditions - Shefali Mozumder; F M Jamil Uddin; Md Abdur Rahman Sarkar; Md Harun Rashid; Swapan Kumar Paul; Shubroto Kumar Sarkar; Md Anowarul Haque; Md Humayun Kabir (SAINS TANAH - Journal of Soil Science and Agroclimatology, 2025)
Cotton yield in Bangladesh is often constrained by suboptimal planting times under subtropical conditions.  The present study aimed to evaluate the impact of planting dates on seed cotton yield across four cultivars to identify the optimal timing for profitable production. A three replicated field trial was conducted at the Cotton Research Farm in Gazipur using split-plot design during the cotton growing season of 2022-23.  Four cotton cultivars: DM-3, Rupali-1, Suvra, and CB-12 were planted on five dates at ~15-day intervals from June to August (viz: 5 June, 20 June, 5 July, 20 July, and 5 August). Results showed that planting on 20 July significantly increased seed cotton yield by 2.580 t ha⁻¹ compared to 5 June, while the 5 August planting produced the lowest yield and ginning outturn (8.9%) (P < 0.01). Among cultivars, CB-12 achieved the highest yield (2.14 t ha⁻¹), followed by Rupali-1 (1.93 t ha⁻¹) and DM-3 (1.56 t ha⁻¹). Although no significant interaction was observed between planting date and cultivar, CB-12 consistently performed best on 20 July, with similar trends for the other cultivars. The study emphasizes the significance of choosing the most suitable planting dates and cultivars. Adoption of 20 July as the ideal planting date may enhance productivity, offering valuable guidance for cotton growers, researchers, and policymakers.